NILAI PENDIDIKAN DALAM SIMBOLISME RITUAL SELAMETAN: Studi tentang Tradisi Mitoni di Desa Damarjati Kalinyamatan Jepara - Alfiana, Nur (CV. Amerta Media, 2019)
This study aims to find out how the implementation and meaning of the mitoni tradition with its various samples in the Damarjati Village, Kalinyamatan Jepara. Through the implementation of the mitoni tradition, research also seeks to identify the educational value contained in it. This type of research is qualitative using descriptive analysis method. Data analysis techniques using content analysis (content analysis). The results of this study indicate that in the implementation of Mitoni take the time of the Maghrib, coinciding with the full moon. After the invited guests are complete, then the host issues menus that have been prepared. In addition to the menu, in the mitoni tradition, there are wisdom symbols contained, such as sega golong. Judging from the manufacturing process must be